Looking for answers? Westonci.ca is your go-to Q&A platform, offering quick, trustworthy responses from a community of experts. Our platform offers a seamless experience for finding reliable answers from a network of experienced professionals. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
You just replace x to -3/4;
f(-3/4) = 4 (-3/4) + 1
4 cancels another 4 in denominator
= -3 + 1
= -2
So you have f(-3/4) = -2
f(-3/4) = 4 (-3/4) + 1
4 cancels another 4 in denominator
= -3 + 1
= -2
So you have f(-3/4) = -2
We appreciate your time. Please come back anytime for the latest information and answers to your questions. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.